1976
DOI: 10.1159/000178743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neonatal Androgen on the Activity of Peptidases in the Rat Brain Inactivating Luteinizing Hormone-Releasing Hormone

Abstract: The activity of peptidase enzymes in different brain areas inactivating luteinizing hormone-releasing hormone (LH-RH) was investigated in normal male and female rats and female rats treated neonatally with androgen. Of the two fractions containing peptidase activity, changes were found only in the supernatant (soluble/cytoplasmic) fraction and were restricted to the hypothalamus and cortex. In both these brain areas, peptidase activity was considerably higher in androgen-treated than in normal female rats; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

1976
1976
2005
2005

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Such lesions might occur at various levels of neural organization, e.g. : (1) 'chemo-lesions', such as those involved in synthesis or degradation of neurotransmit ters [16] or LHRH (indeed, elevated activity of an LHRH inactivating peptidase occurs following neonatal androgenization in fe males [19]); (2) 'organizational lesions' re sulting in abnormal neuronal connections at critical sites [20,21], such as the arcuate nucleus of the medial basal hypothalamus or regions which project LHRH fibers to the arcuate nucleus [22], Such lesions in LHRH pulse generation, with consequent inade quate induction of pituitary LHRH recep tors [10,11], would ultimately result in de creased capacities for accumulation and se cretion of gonadotropins, as observed in this study, and suppression of testicular matura tion, as previously reported [1]. Indeed, rats receiving LHRH antiserum postnatally [23] and the mutant LHRH-deficient mouse [24] manifest deficient testicular maturation, similar to that observed following neonatal androgenization [1],…”
Section: Discussionmentioning
confidence: 99%
“…Such lesions might occur at various levels of neural organization, e.g. : (1) 'chemo-lesions', such as those involved in synthesis or degradation of neurotransmit ters [16] or LHRH (indeed, elevated activity of an LHRH inactivating peptidase occurs following neonatal androgenization in fe males [19]); (2) 'organizational lesions' re sulting in abnormal neuronal connections at critical sites [20,21], such as the arcuate nucleus of the medial basal hypothalamus or regions which project LHRH fibers to the arcuate nucleus [22], Such lesions in LHRH pulse generation, with consequent inade quate induction of pituitary LHRH recep tors [10,11], would ultimately result in de creased capacities for accumulation and se cretion of gonadotropins, as observed in this study, and suppression of testicular matura tion, as previously reported [1]. Indeed, rats receiving LHRH antiserum postnatally [23] and the mutant LHRH-deficient mouse [24] manifest deficient testicular maturation, similar to that observed following neonatal androgenization [1],…”
Section: Discussionmentioning
confidence: 99%
“…The ventrolateral subdivision (VMHv1) is a major neural target for estrogen (Pfaff and Keiner, 1973) and estrogen implants in the VMHvl are sufficient to restore lordosis behavior in female rats made nonreceptive by ovariectomy (Rubin and Barfield, 1980). Estrogen activates lordosis through both genomic and nongenomic mechanisms (McEwen et al, 1990) and some of the gene products that may be relevant to lordosis include peptides (Harlan, 19881, receptors (Akesson et al, 1987;O'Connor et al, 1988;Coirini et al, 1989) and enzymes involved in inactivation of transmitters and neuromodulators (Griffiths et al, 1976;Luine and Rhodes, 1983).…”
mentioning
confidence: 99%
“…To our knowledge, developing PEP activity has not been studied so far in females. The GnRH-degrading system is known to be under sex steroid control [43,44,45] and neonatal female rats treated with androgen show higher peptidase activity inactivating mGnRH than normal animals [46]. This control mechanism may be of physiological interest in male rats, in which the plasma testosterone level increases just before birth and during the first postnatal days [47].…”
Section: Discussionmentioning
confidence: 99%